2015
DOI: 10.1186/s12989-015-0088-2
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution and biodurability: Important parameters needed for risk assessment of nanomaterials

Abstract: Biopersistence and biodurability have the potential to influence the long-term toxicity and hence pathogenicity of particles that deposit in the body. Therefore, biopersistence and biodurability are considered to be important parameters needed for the risk assessment of particles and fibres. Dissolution, as a measure of biodurability, is dependent on the chemical and physical properties (size, surface area, etc.) of particles and fibres and also of the suspension medium including its ionic strength, pH, and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
128
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(129 citation statements)
references
References 97 publications
1
128
0
Order By: Relevance
“…The release of toxic ions has the potential to influence the toxicity of NPs [3436]. Most NPs are rarely soluble at normal physiological conditions; however, their dissolution can be accelerated in acidic conditions [37, 38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The release of toxic ions has the potential to influence the toxicity of NPs [3436]. Most NPs are rarely soluble at normal physiological conditions; however, their dissolution can be accelerated in acidic conditions [37, 38].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the differences in dissolution play a crucial role in the gap of toxicological responses between Cu NPs and Cu MPs. In addition, the biopersistence of NPs influences long-term toxicity and is considered to be an important parameter needed for the risk assessment of NPs [36]. Therefore, further studies will be necessary to investigate whether the toxic responses of Cu NPs observed in this study are transient or persistent responses.…”
Section: Resultsmentioning
confidence: 99%
“…Distribution, disposition, and elimination also reveal if a ENMs are persistent. Persistence (biodurability) of ENMs in biological systems is considered one of the main contributors to particle and fiber toxicity (Utembe, et al 2015), since the longer the ENM persists, the higher the risk there is for an adverse outcome. The most classic example of the serious consequences of persistence in toxicology might be asbestos, which is not metabolized and has an estimated clearance half-time measured in years to decades (Churg and Wright 1994).…”
Section: Discussionmentioning
confidence: 99%
“…As the hydrophilic polymer dissolves, drug molecules are released as fine colloidal particles . The high surface area to volume ratio of these fibers further enhances drug dissolution due to the increased contact area to the dissolution media . PG overcomes a significant limitation in the large‐scale manufacture of micro‐ and nanofibrous drug systems, allowing for production rates in excess of kilograms per hour …”
Section: Applicationsmentioning
confidence: 99%